PENGARUH MANAJEMEN TALENTA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KANTOR CAMAT TEMBILAHAN HULU KABUPATEN INDRAGIRI HILIR - Sapriyanda, Sapriyanda; Donal Devi Amdanata (Indragiri Research Center (ingreat), 2023)
This research aims to examine the influence of talent management and work motivation on employee performance at the Tembilahan Hulu Subdistrict Office, Indragiri Hilir Regency. The research results show that talent management has a positive and significant influence on employee performance. Implementation of effective talent management strategies, such as the introduction and development of potential employees and the placement of employees based on their skills and interests, contributes positively to employee performance. Apart from that, work motivation also has a positive and significant influence on employee performance. Intrinsic and extrinsic motivation, such as a sense of accomplishment, responsibility, recognition, and financial incentives, provide additional encouragement for employees to achieve better performance. The practical implication of this research is the importance of developing effective talent management policies and programs and creating a work environment that supports employee motivation. By implementing this strategy, it is hoped that employee performance can be improved, which in turn will have a positive impact on the effectiveness and efficiency of office operations and increase public trust in the services provided.